Design of high-performance, power-efficient optical NoCs using Silica-embedded silicon nanophotonics - Kakoulli, Elena; Soteriou, Vassos; Koutsides, Charalambos; Kalli, Kyriacos (My University, 2015)
With on-chip electrical interconnects being marred by high energy-To-bandwidth costs, threatening multicore scalability, on-chip nanophotonics, which offer high throughput, yet energy-efficient communication, form an alternative attractive counterpart. In this paper we consider silicon nanophotonic components that are embedded completely within the silica (SiO2) substrate as opposed to prior-Art that utilizes die on-surface silicon nanophotonics. As nanophotonic components now reside in the silica substrate's subsurface non-obstructive interconnect geometries offering higher network throughput can be implemented. First, we show using detailed simulations based on commercial optical tools that such Silicon-In-Silica (SiS) structures are feasible, derive their geometry characteristics and design parameters, and then demonstrate our proof of concept by utilizing a hybrid SiS-based photonic mesh-diagonal links network-on-chip topology. In pushing the performance envelope even more, we next develop (1) an associated contention-Aware photonic adaptive routing function, and (2) a parallelized photonic channel allocation scheme, that in tandem further reduce message delivery latency. An extensive experimental evaluation, including utilizing traffic benchmarks gathered from full-system chip multiprocessor simulations, shows that our methodology boosts network throughput by up to 30.8%, reduces communication latency by up to 22.5%, and improves the throughput-To-power ratio by up to 23.7% when compared to prior-Art.
Keywords: Optical waveguides; Nanophotonics; Silicon; Optical refraction; Optical variables control